PENGARUH CURRENT RATIO, RETURN ON ASSET DAN NILAI TUKAR TERHADAP UNDERPRICING - Raden Neneng Rina Andriani (JURNAL AKUNTANSI, 2022)
ABSTRACTThis study aims to determine the Current Ratio, Return On Assets, Exchange Rates and Underpricing in manufacturing companies that do IPO in 2015-2020,  the effect of Current Ratio, Return On Assets and Exchange Rates partially or simultaneously on Underpricing in manufacturing companies that do IPO in 2015-2020. The sampling technique in this study uses purposive sampling. The data analysis technique used in this study is panel data regression. The results of data analysis show that Current Ratio, Return On Assets, Exchange Rates and Underpricing have fluctuating values in manufacturing companies that conduct IPOs in 2015-2020. Then the results also show that Current Ratio has a significant negative effect on Underpricing, then Return On Assets does not have a significant negative effect on Underpricing while Exchange Rates do not have a significant negative effect on Underpricing. Meanwhile, simultaneous Current Ratio, Return On Assets and Exchange Rates have a significant effect on Underpricing.  Keywords : Current Ratio, Return On Assets, Exchange Rates, UnderpricingABSTRAKPenelitian ini bertujuan untuk mengetahui Current Ratio, Return On Asset, Nilai Tukar dan Underpricing pada perusahaan manufaktur yang melakukan IPO tahun 2015-2020, pengaruh Current Ratio, Return On Asset dan Nilai Tukar secara parsial maupun simultan terhadap Underpricing pada perusahaan manufaktur yang melakukan IPO tahun 2015-2020. Tekinik pengambilan sampel yang digunakan dalam penelitian ini adalah purposive sampling. Teknik analisis data yang digunakan dalam penelitian ini adalah regresi data panel. Hasil analisis menunjukkan Current Ratio, Return On Asset, Nilai Tukar dan Underpricing mempunyai nilai yang fluktuatif pada perusahaan manufaktur yang melakukan IPO tahun 2015-2020. Current Ratio berpengaruh negatif signifikan terhadap Underpricing, Return On Asset tidak berpengaruh negatif signifikan terhadap Underpricing dan Nilai Tukar tidak berpengaruh negatif signifikan terhadap Underpricing. Sedangkan, secara simultan. Current Ratio, Return On Asset dan Nilai Tukar berpengaruh signifikan terhadap Underpricing.Kata Kunci: Current Ratio, Return On Asset, Nilai Tukar, Underpricing